'Mapping the Underworld': recent developments in vibro-acoustic techniques to locate buried infrastructure. Issue 3 (30th September 2013) - Rustighi, E.; Muggleton, J. M.
Abstract : A major UK initiative entitled Mapping the Underworld (MTU) is seeking to address the serious social, environmental and economic consequences arising from an inability to locate – accurately and comprehensively – buried utility service infrastructure without resorting to extensive excavations. MTU aims to develop and prove the efficacy of a multi-sensor device for accurate remote buried utility service detection, location and, where possible, identification. One of the technologies to be incorporated in the device is low-frequency vibro-acoustics, and a number of different vibro-acoustic methods for detecting buried infrastructure have been investigated. The latest developments in the vibro-acoustic location research are presented here. Three complementary methods are described, one of which involves direct excitation of the buried asset and the other two require no such direct access. All involve measurement of the ground surface vibration as a result of the excitation, whether of the ground or of the buried asset directly. Together, these techniques constitute a substantial step change in the way buried infrastructure can be detected using vibro-acoustic methods.